Fundamental solutions of generalized bi-axially symmetric Helmholtz equation - Hasanov, Anvar (Complex variables and elliptic equations, 2007)
In this article for the generalized bi-axially symmetric Helmholz equation (GBSHE) in the domain four fundamental solutions expressed by confluent hypergeometric functions of Kummer of three variables are constructed in explicit form. By means of the expansion of the confluent hypergeometric function it is proved that the solutions found have logarithmic singularities at r = 0 .